State policy for managing seismic territories in Kazakhstan - Kangalakova Dana; Satpayeva Zaira; Kangalakov Kanat (E3S Web of Conferences)
Despite the relatively small number of destructive earthquakes in modern times, their numerous faults mean that the danger of earthquakes is still high. The purpose of the study is to study the chronology of the earthquake in the territory of Kazakhstan and its consequences, as well as to identify the features of the state governance system for seismic activity in the territory of the Republic of Kazakhstan. The methods intended to analyze historical facts and describe public policies, as well as visualize maps of tectonic plates in the Almaty city were used in this study. The results showed that the most seismic zone in the Republic of Kazakhstan is the Almaty city, located on 27 tectonic plates. The Almaty city was twice subjected to devastating earthquakes; therefore, the recurrence rate of destructive earthquakes is high. In this regard, an effective earthquake mitigation policy is required to minimize damage. Besides, this study describes the state seismology governance system in Kazakhstan. The study results can be the basis for the development of comprehensive measures intended to reduce the destructive consequences for seismically active zones.